2011
DOI: 10.1016/j.ijgo.2011.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal support as determined by levator ani defect status 6 weeks after primary surgery for pelvic organ prolapse

Abstract: Objective To evaluate whether major levator ani muscle defects were associated with differences in postoperative vaginal support after primary surgery for pelvic organ prolapse (POP). Methods A retrospective chart review of a subgroup of patients in the Organ Prolapse and Levator (OPAL) study. Of the 247 women recruited into OPAL, 107 underwent surgery for prolapse and were the cohort for the present analysis. Major levator ani defects were diagnosed when more than 50% of the pubovisceral muscle was missing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…As regards levator avulsion, our data are consistent with own results in unrelated data sets 23 and results obtained by others, 11 both on ultrasound and on magnetic resonance imaging. As regards excessive distensibility of the levator hiatus, there is no data in the world literature as this is, to the knowledge of the authors, the first study to demonstrate such a relationship.…”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…As regards levator avulsion, our data are consistent with own results in unrelated data sets 23 and results obtained by others, 11 both on ultrasound and on magnetic resonance imaging. As regards excessive distensibility of the levator hiatus, there is no data in the world literature as this is, to the knowledge of the authors, the first study to demonstrate such a relationship.…”
Section: Commentsupporting
confidence: 93%
“…5 Trauma or 'avulsion' of this muscle predisposes to prolapse of the anterior, central and posterior compartments, [6][7][8] and to prolapse recurrence after surgery. [9][10][11][12] Furthermore, there is some evidence that the size of the genital hiatus, or the hiatus of the levator ani muscle, may also be a predictor independently of avulsion, as patients with excessive hiatal distensibility of over 25 cm 2 on maximal valsalva seem to be at an increased risk of support failure. 13 Such imaging studies are supported by data from a clinical study showing that diminished levator ani contraction strength and a widened genital hiatus were associated with increased anatomical prolapse recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of major levator defects has been confirmed on MRI. In a series of 83 women Morgan, et al reported poorer anterior vaginal support in patients with major levator defects 6 weeks after primary surgery for prolapse 55 . The predictive effect of avulsion in prolapse recurrence applies even in women after placement of anterior compartment mesh.…”
Section: Methodsmentioning
confidence: 97%
“…The risk of recurrence appears to increase almost twofold in patients with levator defects (avulsion of the pubococcygeus muscle from the pubic rami) [67][68][69][70].…”
Section: Recommendations For Conservative Therapymentioning
confidence: 99%